HUMANISTIC DISCOURSE AND THE OTHERS - Hillis Miller, J. (Surfaces, 1994)
This essay focuses on the question of otherness as crucial for discussions of culture and humanistic discourse. In developing an idea of the non-concept of the Other, it summarizes articulations of otherness in Lévinas, Lacan, Derrida, and de Man, among others. In conclusion, it addresses the institutional situation of English departments in the United States.